Winning the battle for sales : lessons on closing every deal from the world's greatest military victories - Golden, John, 1965- (McGraw-Hill, 2013)
Revealing the surprising parallel between the steps of successful selling and the steps of successful warfare; this eye opening guide delivers selling best practices based on examples from history's battlefields that you won't soon forget. --